Controlling photoionization using attosecond time-slit interferences - Mikaelsson, Sara (Faculty of engineering, Lund University, 2020)
We study photoemission, the process where electromagnetic radiation interacts with matter and leads to the emission of electrons. This process takes place on an incredibly short time scale, but with the aid of advanced laser technology we can study its dynamics and the quantum mechanical rules that govern it. Here, we study the photoionization of helium with a 3D momentum spectrometer.

A short train of pulses in the extreme ultraviolet spectral regime and with an attosecond time duration were focused together with a few-cycle near infrared laser pulse into a helium gas jet in a spectrometer. The spectrometer measures both the resulting photoions and photoelectrons after the ionization by the combined extreme ultraviolet and infrared light, and the complete three-dimensional momentum distribution can be reconstructed.

In this study the photoelectron distribution was studied while varying the carrier-to-envelope phase (CEP) of the infrared field. The CEP is the phase relation between the envelope of a light pulse and its carrier wave, and for few cycle pulses it significantly alters the shape of the electric field. Since the attosecond extreme ultraviolet pulses are generated by non-linear up-conversion of the infrared pulse, changing the CEP also influences the number of extreme ultraviolet pulses generated, and the resulting photoelectron momentum distribution also shows great variation that depends on the CEP.

Data has been aquried with a 3D momentum spectrometer, recording position and time-of-flight of photo-electrons and photo-ions in coincidence. For more information about the operation of the spectrometer and methods for retriving momenta see:
M Gisselbrecht, A Huetz, M Lavollée, TJ Reddish, DP Seccombe, Optimization of momentum imaging systems using electric and magnetic fields. Rev. Sci. Instrum. 76, 013105 (2005).

Both measurements were been acquired with an extracting electric field of 84 V and corresponding magnetic field of 5.68 Gauss.

Each measurement consists of three files. The one called 'events' lists the events of the ion and electron detector in chronological order. NaN indicates no event was recorded. The file called 'ions' contains the time and position information of the recorded ions, with each row number corresponding to that recorded in the 'events' file. The file called 'electrons' contains the time and position information of the recorded electrons, with each row number corresponding to that recorded in the 'events' file. For both the 'ions' and 'electrons' file, column one and two contains the x and y information, while column three contains the time of flight in ns.

Vi studerar photojoinsering, processen då interaktionen med elektromagnetisk strålning interagerar med material och leder till frisläppning av elektroner. Detta förlopp är otroligt snabbt, men med hjälp av avancerad laser teknik kan vi studera dess dynamik och de kvantmekaniska regler som är inblandade. I denna studie studerar vi fotojonisering av helium med en 3D momentum spektrometer.

Ett kort pulståg i den extrema ultravioletta spektralregimen och med en attosekund varaktighet fokuserades tillsammans med en ultrakort infraröd laserpuls i en heliumgasjet i en spektrometer. Spektrometern mäter både de resulterande foto-joner och foto-elektroner efter jonisering med det kombinerade extrema ultravioletta och infraröda ljuset, och den kompletta tredimensionella momentdistributionen kan rekonstrueras.

I denna studie studerades fotoelektrondistributionen med en varierande "carrier-to-envelope"-fas (CEP) för det infraröda fältet. CEP är fasförhållandet mellan intensitetsmaxima för en ljuspuls och dess bärvåg, och för ljuspulser som endast har en varaktighet på ett litet antal perioder förändrar denna fas betydligt det elektriska fältets form. Eftersom de extrema ultravioletta pulserna genereras genom icke-linjär uppkonvertering av den infraröda pulsen, påverkar en förändring av CEP:n också antalet extrema ultravioletta pulser som genereras, och den resulterande fotoelektronmomentfördelningen visar också stor variation som beror på CEP.
Controlling photoionization using attosecond time-slit interferences
Keywords: photoelectric effect; fotoelektrisk effekt; attosecond pulses; attosekudpulser; photoionization; fotojonisering; electron momentum spectroscopy; elektronspektroskopi; SCIENCE AND TECHNOLOGY; VETENSKAP OCH TEKNOLOGI; Physical Sciences; Fysik; Atom and Molecular Physics and Optics; Atom- och molekylfysik och optik